Answer:
i) 28 - 30i
ii) 36 + 28i
Explanation:
i) x = 6 + i ⇒2x = 2(6 + i) = 12 + 2i
z = 4 - 8i ⇒ 4z = 4(4 - 8i) = 16 - 32i
2x + 4z = (12 + 2i) + (16 - 32i) = 28 - 30i
ii) w = -1 + 5i and z = 4 - 8i
w × z = (-1 + 5i)(4 - 8i) = -4 + 8i + 20i - 40
⇒collect like terms
w × z = -4 + 28i - 40
![i^(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t72y95o780ylpb8wiaqkgiuf98t02vmt5t.png)
∵
![i^(2)=-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/r3bfv3k7sa7c0u2xu5mayqlao0fbah24lo.png)
∴w × z = -4 + 28i - 40(-1) = -4 + 28i + 40 = 36 + 28i